2021
DOI: 10.1097/mpg.0000000000002941
|View full text |Cite
|
Sign up to set email alerts
|

ITGB2 (Integrin β2) Immunomodulatory Gene Variants in Premature Infants With Necrotizing Enterocolitis

Abstract: Aberrant toll-like receptor (TLR) activation is central to necrotizing enterocolitis (NEC) pathogenesis. β2 integrins regulate TLR signaling, and integrin β2 (ITGB2) deficiency causes TLR hyperresponsiveness. To test the hypothesis that ITGB2 genetic variants modulate NEC susceptibility, we sequenced the exonic ITGB2 locus to compare the prevalence of deleterious variants among 221 preterm infants with and without NEC. ITGB2 variants were not associated with NEC in our entire cohort (NEC [9/56] versus controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…They found that the upregulation of ITGB2 in NSCLC cell lines increased the expression of immune-related proteins, such as N-cadherin, snail, and slug, while decreasing the E-cadherin expression, laying the foundation for further research on immunotherapy. Regarding the non-tumor disorders, studies suggested that the upregulated mRNA expression level of ITGB2 in PBMCs (peripheral blood mononuclear cells) did not associate with disease severity of SSc patients, nor did the status in premature infants with NEC [ 36 , 37 ]. Our results highlight the potential ability of ITGB2 to be a regulator of immune infiltration and a marker of the response to immunotherapy for ovarian cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the upregulation of ITGB2 in NSCLC cell lines increased the expression of immune-related proteins, such as N-cadherin, snail, and slug, while decreasing the E-cadherin expression, laying the foundation for further research on immunotherapy. Regarding the non-tumor disorders, studies suggested that the upregulated mRNA expression level of ITGB2 in PBMCs (peripheral blood mononuclear cells) did not associate with disease severity of SSc patients, nor did the status in premature infants with NEC [ 36 , 37 ]. Our results highlight the potential ability of ITGB2 to be a regulator of immune infiltration and a marker of the response to immunotherapy for ovarian cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of ITGB2 was upregulated in atheroma plaque compared with intact tissue and involved in the development of carotid atherosclerosis [ 28 ]. Moreover, ITGB2 deficiency causes the hyperresponsiveness of the aberrant Toll-like receptor and leads to necrotizing enterocolitis pathogenesis [ 29 ]. In cancer studies, ITGB2 was found to be significantly elevated in high-malignant gliomas and related to a worse prognosis [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…ITGB2 is an inflammatory and immune‐related gene that participates in the inflammatory response and inflammatory tumour transformation during IBD carcinogenesis. 18 , 19 Another study reported that ITGB2 is closely associated with EMT in colorectal cancer (CRC). 20 IBD is closely associated with CRC, and patients with IBD are at higher risk of developing CRC.…”
Section: Introductionmentioning
confidence: 99%